Subjective behavioral measures in myopic and pre-myopic children before and after the COVID lockdown - Alvarez-Peregrina, Cristina; Ruiz-Pomeda, Alicia; Martinez-Perez, Clara; Prieto-Garrido, Francisco Luis; Villa-Collar, Cesar; Gonzalez-Perez, Mariano; Gonzalez-Abad, Ana; Sanchez-Tena, Miguel Angel (Frontiers in Medicine, 2023)
Background There are environmental factors that may contribute to the onset of myopia. This study aims to evaluate the children’s lifestyle changes before and after the COVID-19 lockdown and how they can influence their vision. Methods The same questionnaire was administered to children aged between 5 and 7 in Spain every year in September before (2017–2019) and after the COVID-19 lockdown (2020–2021). All the children also passed a vision exam consisting of the measurement of visual acuity (VA) and determination of objective and subjective refraction. Children were classified as myopes, pre-myopes, or hyperopes. The cut-off points to define the refractive error were established according to the value of the spherical equivalent (SE): hyperopia (SE > +0,75D), myopia (SE ≤ −0,5D), or pre-myopia (−0.5D < SE ≥ +0.75D). Data analysis is performed with the SPSS 27.0 software (SPSS Inc., Chicago, Illinois). Results In the pre-COVID period, the pre-myopes were the ones who spent the longest time outdoors, and after the COVID lockdown, there were no differences between groups. There neither were any differences in the time spent doing near-work activities between the groups in both periods (p > 0.05). Regarding the spherical equivalent, in the pre-COVID period, the mean value was 0.75 ± 2.09D and after the COVID lockdown, it was 0.47 ± 1.88D (p < 0.001). Conclusion Pre-myopes spent more time outdoors than myopes in the pre-COVID period, while myopes spent more time using digital devices. All these differences do not exist after the COVID lockdown, with a general increase in the time spent outdoors and a decrease in the use of digital devices. Further studies are needed to know if these lifestyle changes remain and how they influence the onset of myopia.